KUDUS TRAFFIC POLICE UNIT EFFORTS IN IMPROVING DRIVING LICENCES RENEWAL SERVICES QUALITY THROUGH SIM BOOKING TO ESTABLISH SERVICE EXCELLENT - Roland Risky Joshua Sitorus (Advances in Police Science Research Journal, 2022)
Increased driving licences issuance services at the Kudus Police Station are dominated by renewal driving licences services. However, the increased number of applicants for driving licence extended services affects service quality. The phenomenon resulted in the Traffic Police Unit unable to provide the driver's demands to get excellent service. Kudus Police station tried to accommodate the driver's demands using SIM Booking service. This study aims to describe the implementation of driving licence renewal service using SIM Booking services and find out the efforts of Police Traffic Units to improve driving licence renewal services through SIM Booking services to establish Excellent Service. In analyzing the problem, the author uses the concept of public service by examining the essential components of public service, the concept of excellent service, theory of management elements, and theory of service quality. This study uses a qualitative approach, using analytical descriptive research methods and field research data collection techniques with interviews, observations, and document studies.The study results indicate that implementing driving licences renewal services using SIM Booking has not fulfil the standard service components. The study also found the officer's competence was not yet qualified, and the timing of service delivery was not suitable. Efforts have been made to improve services by providing fast and convenient service, providing comfortable service rooms, showing empathy, and implementing service motto. Factors that influence internally are incompetent personnel, methods that have not been able adapting to conditions, and the local community's characteristics. The author concludes that the implementation has not been maximized because it has not fully met the service standard components, and Kudus Traffic Police have attempted to improve services based on service quality dimensions. the author suggests Kudus Police Station coordinate with the HR department to be allowed to participate in higher education and certification opportunities, adjust to local community situations and conditions, implement cashless payment using QRIS and start utilizing SIM Nasional presisi issued by korlantas.